The State of Environmental Communication Research: An Analysis of Published Studies in the Communication Disciplines - Ki, Eyun-Jung; Shin, Sumin; Oh, Jeyoung (Journal of Intelligent Communication, 2022)
The purpose of this investigation was to systematically evaluate environmental communication studies across the communication-related disciplines. This study achieved the goal by examining published articles in 28 journals from the time period spanning 1973-2014. A total of 142 articles were evaluated based on an analysis of authorial, topical, theoretical, and methodological information. The findings demonstrate exponential growth in the number of environmental communication studies in recent years. A wide range of scholars and institutions has contributed to this area of research. A majority of the articles focused on environmental issues. The outcome of this study could provide a comprehensive picture of communication-based environmental research and guide the directions of future research in this area.